(untitled) (Iranian Journal of Kidney Diseases, 2021)
A 22-year old man underwent kidney transplant two years ago. Following fever and cough, epigastric pain, convulsion, vomiting and PO intolerance he had been brought to the emergency room. During evaluation in addition to pulmonary involvement with SARS-COVID-19, brain, stomach and pancreas involvements with COVID-19 infection also were detected. Hemodialysis and specific treatments were initiated. After 16 days he could be discharged ultimately.